Differentiated instruction in mover kindergarten: A model implementation with merdeka curriculum - Ika Maryani; Ristiyati Ristiyati; Suyatno Suyatno (Journal of Early Childhood Care and Education, 2023)
This study formulated a model for differentiated instruction at a kindergarten and described the factors that promoted or inhibited its implementation. A qualitative case study design was employed. The data were gathered through interview, observation, and documentation. The study involved a kindergarten principal, two kindergarten teachers, and 15 students from Aisyiyah Bustanul Athfal kindergarten as the mover school. Researchers were assisted by an interview guideline, an observation guideline, and documentations. Data analysis was performed based on Miles and Huberman’s interactive model. The data were validated through source and technique triangulation. Differentiated instruction was conducted using the center learning model, using demonstration, outing-class, and role-playing methods. Factors that facilitated the differentiated instruction implementation at the kindergarten included a supportive, safe, and comfortable learning environment, sufficient resources and materials, students’ psychological conditions and preparedness for learning, and the active engagement of school communities inside and outside the school. Factors that promoted the process comprised the scarcity of learning resources, insufficient infrastructure, a shortage of qualified educators, and the psychological well-being of students during the learning process. The instructional media used for the instruction were loose parts and natural materials surrounding the children.